Blastocysts originated from oocytes with smooth endoplasmic reticulum aggregates have a reduced euploidy rate: a retrospective cohort study - Kong, Pengcheng; Pan, Jiaping; Liang, Shanshan; Yin, Mingru; Teng, Xiaoming (Frontiers in Endocrinology, 2024)
Research question: Does the presence of smooth endoplasmic reticulum aggregates (SERa) in oocytes adversely impact the euploidy rate of subsequent blastocysts？ Design: We performed a retrospective cohort study with 671 young patients (< 38 years) undergoing their first preimplantation genetic testing for aneuploidy (PGT-A) between January 2019 and October 2022 at a reproductive medical center of university affiliated teaching hospitals in China. Cycles were categorized as either SERa(+) cycles (containing at least one SERa(+) oocyte) or SERa(-) cycles (all oocytes without SERa).In SERa(+) cycles, oocytes were further subdivided into the SERa(+) oocyte group and the sibling SERa(-) oocyte group, comprising oocytes with normal morphology.Results: No significant differences were observed in the normal fertilization rate (72.9% vs. 75.4% vs. 72.6%, P=0.343), and cleavage rate (96.8% vs. 97.1% vs. 96.4%, P=0.839) among the SERa(-) cycle group, the SERa(-) oocyte group, and the SERa(+) oocyte group. Additionally, there were no statistically significant differences in the rates of good quality embryos (44.7% vs. 48.8% vs. 46.2%, P=0.177) or blastocyst formation (60.1% vs. 60.9% vs. 60.5%, P=0.893) among the groups. However, the euploidy rate of blastocysts derived from SERa(+) oocytes was significantly lower compared to those from SERa(-) oocytes in SERa(+) cycles and normal oocytes in SERa(-) cycles (39.3% vs. 51.2% vs. 54.5%, P=0.005). Despite this, there were no significant differences in pregnancy and neonatal outcomes after euploid embryo transfer among the three groups.Conclusions: Blastocysts derived from SERa(+) oocytes have a lower euploidy rate than those derived from SERa(-) oocytes. Nevertheless, comparable reproductive outcomes were achieved following euploid embryo transfer from both SERa(+) and SERa(-) oocytes.